Genetic predisposition may not improve prediction of cardiac surgery-associated acute kidney injury - Douville, Nicholas J.; Larach, Daniel B.; Lewis, Adam; Bastarache, Lisa; Pandit, Anita; He, Jing; Heung, Michael; Mathis, Michael; Wanderer, Jonathan P.; Kheterpal, Sachin; Surakka, Ida; Kertai, Miklos D. (Frontiers in Genetics, 2023)
Background: The recent integration of genomic data with electronic health records has enabled large scale genomic studies on a variety of perioperative complications, yet genome-wide association studies on acute kidney injury have been limited in size or confounded by composite outcomes. Genome-wide association studies can be leveraged to create a polygenic risk score which can then be integrated with traditional clinical risk factors to better predict postoperative complications, like acute kidney injury. Methods: Using integrated genetic data from two academic biorepositories, we conduct a genome-wide association study on cardiac surgery-associated acute kidney injury. Next, we develop a polygenic score and test the predictive utility within regressions controlling for age, gender, principal components, preoperative serum creatinine, and a range of clinical risk factors. Finally, we estimate additive variant heritability using genetic mixed models. Results: Among 1,014 qualifying procedures at Vanderbilt University Medical Center and 478 at Michigan Medicine, 348 (34.3%) and 121 (25.3%) developed AKI, respectively. No variants exceeded our predetermined threshold for genome-wide significance (P < 5 x 10-8), however, six previously unreported variants exceeded the suggestive threshold (P < 1 x 10-6). Notable variants detected include: (i) rs74637005, located in the exonic region of NFU1 and (ii) rs17438465, located between EVX1 and HIBADH. We failed to replicate variants from prior studies of post-surgical acute kidney injury. Polygenic risk was not significantly associated with acute kidney injury in any of the models, however, case duration (aOR=1.002, 95% CI 1.000-1.003, P=0.013), diabetes mellitus (aOR=2.025, 95% CI 1.320-3.103, P=0.001), and valvular disease (aOR=0.558, 95% CI 0.372-0.835, P=0.005) were significant in the full model. Conclusions: Polygenic score was not significantly associated with post-cardiac surgery acute kidney injury and acute kidney injury may have low low heritability in this population. These results suggest that susceptibility is only minimally influenced by baseline genetic predisposition and clinical risk factors, some of which are modifiable, may play a more influential role in predicting this complication. The overall impact of genetics in overall risk for cardiac surgery-associated acute kidney injury may be small compared to clinical risk factors.